2018
DOI: 10.1111/joid.12131
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Hiring Practitioner Preferences for and Assessment Practices of Prospective Candidates

Abstract: While the decision‐making strategies involved in the design process have long been a topic of scholarly exploration, less attention has been devoted to probing the likely antecedents to other decisions that potentially influence design practice. One such decision is the formation of a project team, which is likely influenced by those who are hired to work in a firm. While some interior design scholars have outlined the skills and characteristics viewed as most desirable by hiring practitioners, there remains r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Also, we consider that it is important to know what factor of employability is important for practitioners: soft skills, hard skills or specific ones [5,35] because this could depend on the sector of activity, i.e., fortheinterior design sector, it prioritizes soft skills when screening candidates [35] but for a graduate, both hard and soft skills are rated equally important by employers overall [28].We mention that for the hard and soft skills, we refer to the accepted definitions of the international organizations for hard skills [36] as per the OECD definition, "the technical and analytical competencies and know-how that allow the worker to perform the mechanical aspects of a job" and for the soft skills, the integrated definition of UNECO [37], FAS [37] and European Union Commission [25], respectively:…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, we consider that it is important to know what factor of employability is important for practitioners: soft skills, hard skills or specific ones [5,35] because this could depend on the sector of activity, i.e., fortheinterior design sector, it prioritizes soft skills when screening candidates [35] but for a graduate, both hard and soft skills are rated equally important by employers overall [28].We mention that for the hard and soft skills, we refer to the accepted definitions of the international organizations for hard skills [36] as per the OECD definition, "the technical and analytical competencies and know-how that allow the worker to perform the mechanical aspects of a job" and for the soft skills, the integrated definition of UNECO [37], FAS [37] and European Union Commission [25], respectively:…”
Section: Literature Reviewmentioning
confidence: 99%
“…These were determined by careful analysis of the scope, duration and structure of the internship experience during a curriculum self-study process. Also, the internship helps students “examine key business issues”, which align with CIDA Standard 6: Business Practices and Professionalism (Huber, 2018, p. 24). These student learning expectations are created by CIDA and are indicated in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…An internship can influence a student's career readiness (Salvadge, 2019). It can increase a student's employability with faster hiring in an entry-level position, higher salary and greater overall job satisfaction (Huber, 2018; Reddan and Rauchle, 2012; Saltikoff, 2017). Employers also benefit from internships, such as better employee recruitment (Wanless, 2013), reduced cost for basic work (Coco, 2000) and an infusion of new ideas (Tovey, 2001).…”
Section: Internshipmentioning
confidence: 99%
“…In terms of information acquisition, a separate study found that nearly half of designers conducted interviews and focus groups with project stakeholders, though only 30% conducted on-site observations (Huber, 2016a). Evidence also revealed possible issues involving interpretation, such that designers reported rapidly reviewing information sources (Huber, 2018a) and have prioritized heuristics and relatively subjective strategies in other decision-making tasks (Huber, 2018b).…”
Section: Journal Of Interior Designmentioning
confidence: 99%
“…Educators may also opt to involve their students in data collection modes involving diachronic communication. In addition to offering valuable project insights, exposure to these methods could foster those skills that students need to develop, such as communication prowess (Huber, 2018b), proper vetting of information sources (Huber, 2016a), and reflective design practices (Lawson, 2005).…”
Section: Educatorsmentioning
confidence: 99%